Music therapy research in dementia: fostering a global approach. Issue 1 (1st June 2016) - Tamplin, Jeanette; Clark, Imogen; Ridder, Hanne Mette; McDermott, Orii; Odell-Miller, Helen; Laitinen, Sari; Gold, Christian
Abstract : Background : The number of people living with dementia is reaching crisis proportions. Consequently, music therapy researchers worldwide are attracting large grants to examine the impact of music participation on the health and wellbeing of people with dementia. Objective : To foster international collaborations and a shared research agenda amongst researchers investigating the impact of music therapy for people with dementia. Methods : Round table contributors will consider the following questions: What is the current state of music therapy research in dementia? What are our primary research focus areas (e.g. wellbeing, carers, cognition)? What research methods and outcome measures best capture the impact of music therapy for people with dementia? What is the potential for international research collaboration? Conclusions : Music therapy research collaborations could strengthen research in dementia with potential for larger participant samples, multicultural perspectives, consistent use of outcome measures, and thus a richer knowledge base from which to interpret findings.